2004
DOI: 10.1111/j.1440-1797.2004.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effect of Hemidesmus indicus, a herbal drug used in gentamicin‐induced renal toxicity

Abstract: The treatment with H. indicus helped in the management of renal impairment, which was induced by gentamicin in rats. This is evident from the results obtained for various kidney function tests for gentamicin, along with the results from the plant treated group, and is in comparison with the results found for the gentamicin recovery group. A histological examination of kidneys also supports the findings from haematological evaluations. The plant shows promise as an adjunct therapy along side aminoglycosides as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…Gentamicin and ethanol-induced oxidative stress and thereby caused renal toxicity in rats, and administration of H. indicus root extract has been shown to reduce the toxicity by preventing the free radical-mediated oxidative stress in the tissues (Kotnis et al, 2004;Saravanan & Nalini 2007a, 2007b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gentamicin and ethanol-induced oxidative stress and thereby caused renal toxicity in rats, and administration of H. indicus root extract has been shown to reduce the toxicity by preventing the free radical-mediated oxidative stress in the tissues (Kotnis et al, 2004;Saravanan & Nalini 2007a, 2007b.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to that of A. calamus, the root extract of H. indicus also possesses strong antioxidant and radioprotective properties (Shetty et al, 2005). The root extract of this plant has been reported to be a potent chemopreventive agent in skin carcinogenesis (Sultana et al, 2003) and was also found to be effective against renal toxicity induced by ethanol and aminoglycoside antibiotics as well as ethanol-mediated hepatic toxicity in experimental animals (Kotnis et al, 2004, Saravanan & Nalini, 2007a, 2008. One of the major active principles in the root extract has been identified as 2-hydroxy 4-methoxy benzoic acid, which help to reduce the levels of liver collagen, hydroxyproline content, crosslinked fluorescence, shrinkage temperature and lipid peroxidation in ethanol-fed rats (Saravanan & Nalini, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“… Hemidesmus cools the urinary tract, which effective alleviates the burning sensation during urination.The herb also useful in treating UTI & kidney disorders. [27,28]  Effective as anti inflammatory [29], diuretic [27]& vulnerary and syphilis.Hemidesmus is often combined with herb Picrorrhiza and used for Syphilis.…”
Section: Medicinal Propertiesmentioning
confidence: 99%
“…Evidentially, this plant have been reported to be used as hypoglycemic, hypolipidemic [14] , antioxidant, antithrombotic [25] , tranquilizer [26] , anti-inflammatory, anti-pyretic [27] , antiulcerogenic [28] , cardioprotective [29,30] , hepatoprotective [31] , renoprotective [32] , genotoxic and anti-genotoxic [33] , radioprotective [34] , neutralization of viper venom [35] , anti-bacterial and larvicidal. [36] The objective of the present research work was to investigate the antihyperlipidemic activity of biofraction of water extract of root of H.indicus by studying in vivo effect on poloxamer p-407 induced hyperlipidemia in rats.…”
Section: Indicusmentioning
confidence: 99%